Optimal adaptive control and differential games by reinforcement learning principles - Vrabie, Draguna L.; Vamvoudakis, Kyriakos G.; Lewis, Frank L. (The Institution of Engineering and Technology, 2013)
The book reviews developments in the following fields: optimal adaptive control; online differential games; reinforcement learning principles; and dynamic feedback control systems.